Appropriate Use Of Translation Techniques In Different Text Types Translation Project Submitted - Bakary, S.A. (University of Ghana, 2021)
Abstract The ability to choose the correct translation technique is indispensable; therefore, it is essential for translators to be cognizant of why a particular technique is used. This study points out and applies the appropriate translation techniques for the translation of some specific texts. Three documents are selected based on their text type to carry out this study: (i) Individu et société dans le roman négro-africain d’expression anglaise de 1939 à 1986, tome III by Professor Noël Dossou-Yovo (1998), (ii) a magazine ‘Afrique Intégration’ (2006), and (iii) a daily newspaper ‘Le MATINAL’ N° 2358 (2006). A text is extracted from each document and analyzed by showing their typology and how the translation techniques are applied to them with regard to French into English translation. Based on findings, it is discovered that translators especially beginners face some main problems related to cultural contexts, sentence or language structures, and lexical features, as the rules guiding them differ from English to French. Therefore, they carry out their translation without adopting the right techniques or even considering the text type. As a result, this study focuses on problems encountered and how they are solved with the appropriate translation techniques suggested by J.P. Vinay and J. Darbelnet, in application to the translation of the three text types selected. Keywords: translation, translation techniques, text types, typology
MSc. Arts In Translation
Keywords: Translation; Translation techniques; Text types; Typology